2020
DOI: 10.1002/adfm.202006273
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing of Perovskites for Breaking Performance–Temperature Tradeoffs in Fabric‐Based Thermistors

Abstract: A novel low‐temperature route is developed for inkjet printing of the perovskite Cs2SnI6, to create wearable negative‐temperature‐coefficient thermistors with unprecedented performance on thermally sensitive fabrics. A low processing temperature of 120 °C is achieved by creating a stable and printable ink using binary metal iodide salts, which is thermally transformed into dense Cs2SnI6 crystals after printing. The optimally printed Cs2SnI6 shows a temperature measurement range up to 120 °C, high sensitivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…In recent years, fabric based NTC thermistors have been also gaining attention due to the demand in wearable electronic textile industries. For instance, a recent work by Li et al [64] demonstrated that a novel low-temperature route can be used to print such thermistors on polyester fabric, for which perovskite (Cs 2 SnI 6 ) ink can be used. The work by Lall et al [50] demonstrated that temperature sensors printed using silver ink can reach to sensitivity values as high as 0.192%/ • C temperature coefficient of resistance (TCR).…”
Section: Sensorsmentioning
confidence: 99%
“…In recent years, fabric based NTC thermistors have been also gaining attention due to the demand in wearable electronic textile industries. For instance, a recent work by Li et al [64] demonstrated that a novel low-temperature route can be used to print such thermistors on polyester fabric, for which perovskite (Cs 2 SnI 6 ) ink can be used. The work by Lall et al [50] demonstrated that temperature sensors printed using silver ink can reach to sensitivity values as high as 0.192%/ • C temperature coefficient of resistance (TCR).…”
Section: Sensorsmentioning
confidence: 99%
“…The ink characteristics are very important when ejecting the same size and morphology of ink from the nozzle for continuous inkjet printing. [113] Although PIJ is the most stable inkjet method, the solvents and physical properties of the operating ink contribute to the acquisition of accurate perovskite patterns. Li et al introduced different solvents to fabricate highly efficient photovoltaic devices; as shown in Figure 11, they used a solvent composed of n-methyl pyrrolidone (NMP) and dimethyl formamide (DMF) as a replacement for DMSO, which suffers from fast perovskite film growth.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…Li et al presented inkjet-printed Cs 2 SnI 6 , a new thermistor material with a B constant at 4400 K. This material may be formed solely through the printing and drying (at 120 • C) processes. Based on this characteristic, they developed fabric-based thermistors for wearable devices, which may be realized by infiltrating a starting solution into the polyester fabric [64].…”
Section: Thermistor Temperature Sensorsmentioning
confidence: 99%